UPAYA MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN KOLASE - Ida Ridayanti; Sri Meidawaty (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Early Childhood Education (PAUD) is an education that is held with the aim of facilitating the overall growth and development of children starting from the development of aspects of religious and moral values, physical-motor, cognitive, language, social-emotional, and art. All aspects of development are very important to be developed and are expected to develop in a balanced manner from one aspect to another. This shows the importance of efforts to develop children's potential, one of which is the development of creativity by using collage activities which will determine children's success in the future. The objectives of this study are: 1) To improve the process of planning daily activities through collage activities in an effort to increase the creativity of children in class A KB Al-Fatah, Pangandaran District, Pangandaran Regency. 2) Improve the learning process through collage activities in an effort to increase children's creativity in class A KB Al-Fatah Sukahurip, Pangandaran District. 3) Increase children's creativity through collage activities in class A KB Al-Fatah Sukahurip, Pangandaran District. The method used is class action research method, according to Kurt Lewin's model, which has four stages, planning, implementing, observing, and reflecting. The data collection technique is done by using documentation technique and observation technique. Based on the results of the study, the observation of each teacher's performance and the development of creativity has increased, namely as follows: First, the teacher's performance in preparing RPPH in the first cycle the average score was 2.5, in the second cycle with an average score of 3.6. Both teacher performance in the learning process in the first cycle an average score of 3.8 and in the second cycle with an average score of 3.9. The three children's creativity abilities in the first cycle indicator 1 reached an average value of 1.8 = BW, in the second cycle indicator I reached an average value of 3.15 = BSH. In the first cycle indicator 2 with an average value of 2.09 = MB, in the second cycle indicator 2 with an average score of 3.08 = BSH. In cycle I, indicator 3 reaches an average score of 2.21 = MB, in cycle II indicator 3 the average score is 3.05 = BSH. Then in cycle I indicator 4 the average score obtained is 1.84 = BW, in cycle II indicator 4 the average score is 2.97 = MB.